Karakteristik Sifat Mekanik Hasil Pengelasan Gesek Aluminium dengan Tembaga Menggunakan Variasi Kecepatan Putar dan Kekasaran Permukaan Kontak - Iman - Saefuloh; Ipick Setiawan; S Sunardi; Rina Lusiani; S Suryana (Malikussaleh Journal of Mechanical Science and Technology, 2022)
Friction welding is a type of welding that is used for a variety of materials. Friction welding is a method of joining two materials by swiping them together until they reach some of the melting points of the materials to be joined, then applying constant pressure. Aluminum and copper are the materials to be joined in this study. Using rotational speed and contact surface roughness variations. The purpose of this research is to determine the mechanical properties of friction welding results between aluminum and copper. The speed settings are 1230, 1500, and 2500 rpm. Use sandpaper grades #100, #800, and #1500 to achieve different levels of surface roughness. According to the results of this study, the rotational speed with the highest tensile strength and hardness values is 1230 rpm, namely 59.6 MPa and 54.6 HVN (Al), 112.1 HVN (Al) (Cu). In terms of surface roughness variations, the surface roughness using grade #1500 sandpaper has the highest value, namely 54.18 HVN (Al), 112.1 HVN (Cu). And #100 sandpaper with a value of 52.48 Mpa. The results of the microstructure test in the weld joint area at a magnification of 1000x indicated that the friction welding of aluminum and copper was successful, as evidenced by the diffusion of aluminum and copper in this area.